SOCIAL EPIDEMIOLOGY, EDUCATION, AND HEALTH PROMOTION IN INFECTIOUS DISEASE - Souza, Claudia Teresa Vieira de; Nunes, João Arriscado; Hora, Dinair Leal da; Erthal, Regina Maria de Carvalho; Pimentel, Maria Ines Fernandes; Pacheco, Sandro Javier Bedoya (Revista de Patologia Tropical / Journal of Tropical Pathology, 2014)
This short communication discusses a project in Rio de Janeiro involving an attempt at imparting clinical and social epidemiology knowledge through educational initiatives. In small groups, social epidemiology was discussed in the context of a clinical/epidemiological project on various infectious diseases. Relevant knowledge was produced collaboratively by a multidisciplinary team of clinical research and project participants, comprising patients, relatives, friends, and health workers. An improvement in the learning capacity of participants was observed, fostering active appropriation of scientific knowledge. In dealing with infectious disease, social epidemiology contributes to the development of new strategies for collaborative research and disease prevention.